Building Dreams And Achieving Aspirations: Training And Mentoring For Poco Ranaka Ruteng Students - Lena Ellitan; Lina Anatan (Joong-Ki : Jurnal Pengabdian Masyarakat, 2025)
A dream is a perfect desire to be achieved or realized. Having dreams in life is important for students since it provides a picture of their future life. Furthermore, dreams can train or encourage someone to explore their potential to the fullest and foster a fighting spirit in achieving their hopes. In order to build dreams and achieve their goals, 8 teams conducted mentoring activities for students at SMKN 1 Poco Ranaka, a public vocational high school located in Poco Ranaka District, East Manggarai Regency, East Nusa Tenggara Province. This Community Service Program (PKM) activity aims to motivate students of SMK Poco Ranaka to strive to achieve their dreams and have a clearer vision and mission for the future. Community service activities are conducted using several methods including lecture sessions, brainstorming, group discussions, and group presentations. Through lecture sessions, students are provided with knowledge and understanding about dreams and ideals, as well as how to realize those dreams and ideals. In brainstorming sessions, group discussions, and group presentations, students are given the opportunity to creatively gather ideas to explore their dreams and aspirations in solving problems they may face after graduating from school.